The grand domestic revolution : a history of feminist designs for American homes, neighborhoods, and cities - Hayden, Dolores (Cambridge, Mass. : MIT Press, 1981)
"This is a book that is full of things I have never seen before, and full of new things to say about things I thought I knew well. It is a book about houses and about culture and about how each affects the other, and it must stand as one of the major works on the history of modern housing." - Paul Goldberger, The New York Times Book Review
"First MIT press paperback edition, 1982, c1981 by The Massachusetts Institute of Technology."--Title page verso.
Includes bibliographical references and index.
ENH
Keywords: Feminism -- United States; Division of labor; Architecture; Housewives -- United States; Home economics -- United States; Women and socialism -- United States; Architecture, Domestic -- United States